Effectiveness of climate information services: an evaluation of the accuracy and socio-economic benefits for smallholder farmers in Niger and Mali - Bizo, Issiaka M.; Traore, Bouba; Sidibé, Amadou; Soulé, Moussa (Frontiers in Climate, 2024)
Climate information services are foundational means of building the farmer's resilience.However, studies are scarce about the accuracy of climate information services in dryland regions such as the West Africa Sahel, like in Mali and Niger. Thus, this study examined the accuracy of climate forecasts and their socio-economic benefits in these two countries. For rainfall forecasts and alerts, we collected the 2022 data from the 'SMS Sandji' platform in Mali (Nara) and the national meteorological agency alert database in Niger (Zinder). The socioeconomic benefits of climate information were determined using a sample of 900 individuals in Niger and 227 in Mali. The results indicate that both seasonal and daily climate forecasts have high to moderate accuracy from 0.7 to 0.58 for CSI and 0.11 to 0.43 for BS index in Niger, and 0.94 to 0.91 for CSI, and 0.06 to 0.25 for BS in Mali. The results of field survey show that, in general, 87% to 100% of the respondents in Niger and 100% in Mali received the seasonal forecasts. ANOVA also reveals with high significance (p value = 0.0001) that the utilization of climate information plays a crucial role in improving farmers' average financial incomes with FCFA 24,943 per hectare at season onset to FCFA15,355 per hectare during the cropping season, and FCFA 6204 per hectare at the end of the season, and time-saving of 36 hours per hectare to 8 hours per hectare, depending on the period when the information was used. Globally, this work underscores the importance of climate information services and highlights their positive socioeconomic impacts to the livelihood of farmers.